MENDETEKSI REDUNDANSI PASANGAN KALIMAT DALAM DOKUMEN SPESIFIKASI KEBUTUHAN PERANGKAT LUNAK DENGAN PENDEKATAN KEMIRIPAN SEMANTIK - Enny Dwi Oktaviyani; Licantik Licantik (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
Software Requirements Specification Document must be complete, unambiguous and correct because an incorrect Software Requirements Specification Document can lead to failure in software development. Software Requirements Specification document must contain non-redundant sentences. Meyer's Seven Sins describes several errors in Software Requirements Specification Document, one of which is redundancy which is a variant of noise. Redundancy is the repetition of the same information, but using different terms or phrases, thus giving the impression that new information is available. This study analyzes the performance of the framework and tools for detecting redundancy in sentence pairs in the software requirements specification document using the WordNet-based semantic similarity method. This study tries to develop the framework and tools that have been proposed in previous studies, namely by detecting redundancy in sentence pairs without fact extraction. The proposed approach and evaluation process uses Kappa values ??to determine whether the performance of the framework and assistive tools can be used to detect redundancy in sentence pairs properly. The method using literature study, data collection, problem analysis, making a framework, making auxiliary tools, and testing. The test uses the Kappa value with two scenarios, from the results of testing the framework and assistive tools can be used to detect redundancy in the Software Requirements Specification Document with a Kappa value of 0.777 with the interpretation of the kappa value is a substantial agreement at a threshold of 0.73